2017
DOI: 10.1007/s10637-017-0453-0
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and clinicopathological features of nivolumab-related cholangitis in patients with non-small cell lung cancer

Abstract: Background Nivolumab demonstrates promising efficacy for the treatment of non-small cell lung cancer and other malignancies. The clinical benefit of nivolumab, however, may be hampered by specific immune-related adverse events (irAEs), and little is known regarding nivolumab-related cholangitis. Methods A computerized search of our clinical database identified 3 metastatic non-small cell lung cancer patients with nivolumab-related cholangitis. All patients were treated with intravenous nivolumab monotherapy (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(128 citation statements)
references
References 24 publications
7
106
0
Order By: Relevance
“…Cholangitic liver diseases have also been reported, although rare. (2) These cases include avelumab (3) and nivolumab (4,5) related cholangitis, which present similar images ( Fig. 1) and patterns of CD8-positive T-cell infiltration into the bile duct ( Fig.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Cholangitic liver diseases have also been reported, although rare. (2) These cases include avelumab (3) and nivolumab (4,5) related cholangitis, which present similar images ( Fig. 1) and patterns of CD8-positive T-cell infiltration into the bile duct ( Fig.…”
Section: Discussionmentioning
confidence: 86%
“…However, further studies are necessary to establish the optimal management of patients with this immunotherapy-related SSC. (2,4) These findings suggest that the possibility of SSC should be considered when administering immune checkpoint inhibitors to patients.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Kawakami et al . reported that nivolumab‐related cholangitis was characterized by: (i) extrahepatic bile duct dilation without obstruction; (ii) diffuse hypertrophy of the extrahepatic bile duct wall; (iii) increase of the biliary enzymes ALP and GGT relative to the hepatic enzymes AST and ALT; (iv) absence of the serum immunological markers ANA, AMA, smooth muscle antibody, and IgG4; (v) the pathological finding of CD8 + T cell infiltration in the portal area by liver biopsy; and (vi) a moderate to poor response to steroid therapy . The present case showed most of these features.…”
Section: Discussionmentioning
confidence: 98%
“…Among irAEs, cholangitis is rare and its clinicopathological features and management remain unclear. There are some reports about nivolumab‐related cholangitis that describe its imaging and clinicopathological features . Ogawa et al .…”
Section: Discussionmentioning
confidence: 99%